Numerical investigations and performance comparisons of a novel cross-flow hollow fiber integrated liquid desiccant dehumidification system. (1st September 2019) - Zhang, Nan; Chen, Xiangjie; Su, Yuehong; Zheng, Hongfei; Ramadan, Omar; Zhang, Xingxing; Chen, Hongbin; Riffat, Saffa
Abstract: The heat and mass transfer process of a novel cross-flow hollow fiber integrated liquid desiccant dehumidification system is analyzed numerically. Compared with other porous media or packing towers in dehumidification applications, hollow fibre membranes have significant advantages including low weight, corrosion resistance and no liquid droplet carryover. A novel air-KCOOH cross-flow dehumidification system was designed and manufactured, with 5500 hollow fibres formed into a circular module. The variations of the dehumidification effectiveness and moisture removal rates were studied numerically and validated against experimental results under the incoming air mass flow rates of 0.08–0.26 kg/s and relative humidity from 55% to 75%. The dehumidification performance comparisons for the proposed system using CaCl2, LiCl and KCOOH as the desiccants have been conducted. The results demonstrated that under the same m*(ratio between solution mass flow rate to the air mass flow rate), the proposed system using 62% KCOOH could achieve approximately the same latent effectiveness compared with 40% CaCl2 and 32% LiCl, with at least 3.1% sensible effectiveness improvement. Therefore, it could be concluded that the proposed system using KCOOH as desiccant could be more applicable for dehumidification purpose compared with other systems using conventional liquid desiccants.